On mono-W signatures in spin-1 simplified models - Ulrich Haisch; Felix Kahlhoefer; Tim M.P. Tait (Physics Letters B, 2016)
The potential sensitivity to isospin-breaking effects makes LHC searches for mono-W signatures promising probes of the coupling structure between the Standard Model and dark matter. It has been shown, however, that the strong sensitivity of the mono-W channel to the relative magnitude and sign of the up-type and down-type quark couplings to dark matter is an artifact of unitarity violation. We provide three different solutions to this mono-W problem in the context of spin-1 simplified models and briefly discuss the impact that our findings have on the prospects of mono-W searches at future LHC runs.